Seleksi Generasi Menengah Galur-Galur Padi Rawa Tahan Hawar Daun Bakteri Berdasarkan Indeks Seleksi Terboboti - Wening, Rina Hapsari; Supartopo, Supartopo; Supartopo, Supartopo; Rumanti, Indrastuti Apri; Rumanti, Indrastuti Apri; Samaullah, M. Yamin; Samaullah, M. Yamin (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2018)
Increasing of significant population also resulted in increased national food needs. Conversion of arable land into non-agricultural land make suboptimal lands became the target of planting areas to fulfill food security. Swamp land is one of suboptimal land which potential to be developed. Swamp land in Indonesia (33.40 to 39.40 million ha) has a huge potential to support the stability of the national rice production. In addition to abiotic stresses, biotic stresses also often occurs in swamp lands. This study aims to select the lines which have high yield and resistant to bacterial leaf blight (BLB). This experiment was conducted at Muara, Bogor in April-September 2014. The materials are 318 lines with five check varieties namely Inpara 2, Inpara 3, Inpara 6, Inpara 7, and IR42. The experiment was arranged in a augmented design. Observation were made on plant height, tiller number, age of flowering, age of maturity, yield, scores of bacterial leaf blight (BLB), and a score of phenotypic acceptability (PACP). Data were analyzed using SAS version 9 for analysis of variance and continue with path analysis and weighted standardized selection index. The results showed that there were sixty lines selected based on weighted standardized selection index. The lines have a yield between 4.48 to 7.48 t / ha and promissing to the next test. Three lines have yield which significantly higher than Inpara 2 namely B13100-2-MR-2-KA-3-2 (7.48 t / ha), TDK-Sub 1 1- MR-1 (7.04 t / ha), and B13991E-KA-25 (6.98 t / ha). TDK-Sub 1 1- MR-1 and B13991E-KA-25 also have resistance to bacterial leaf blight.